Inhibition of growth of Leishmania mexicana mexicana by Leishmania mexicana amazonensis during "in vitro" co-cultivation Inibição do crescimento de Leishmania mexicana mexicana por Leishmania mexicana amazonensis durante o co-cultivo "in vitro" - Raquel S. Pacheco; Gabriel Grimaldi Júnior; Carlos M. Morel (Memorias do Instituto Oswaldo Cruz, 1987)
Inhibition of one Leishmania subspecies by exometabolites of another subspecies, a phenomenon not previously reported, is suggested by our recent observations in cell cloning experiments with Leishmania mexicana mexicana and Leishmania mexicana amazonensis. Clones were identified using the technique of schizodeme analysis. The phenomenon observed is clearly relevant to studies of parasite isolation, leishmanial metabolism, cross-immunity and chemotherapy. Inhibição do crescimento de um subespécie de Leishmania por exometabólitos de outra subespécie, um fenômeno ainda não notificado, é sugerido em nossas recentes observações em experimentos de clonagem celular com Leishmania mexicana mexicana e Leishmania mexicana amazonensis. Os clones foram identificados usando a técnica de análise de esquizodemas. O fenômeno observado é claramente relevante em estudos de isolamento parasitário, metabolismo, imunidade cruzada e quimioterapia.